PFAS removal by ultrasound irradiation: pathways, chemistry and operation - Tasca, Andrea Luca; Uwayezu, Jean Noel; Panizza, Marco; Kumpiene, Jurate; Carabante, Ivan (Frontiers in Environmental Science, 2026)
Per- and polyfluoroalkyl substances (PFAS) are synthetic chemicals found worldwide in several industrial and consumer products. The extensive use of these fluorinated organic compounds, together with their high stability, has led to a broad contamination of water and soil resources. Among the technologies under development for their remediation, sonochemistry stands out. Propagation of ultrasounds in aqueous media results in sonophysical and sonochemical effects, able to collaboratively mineralize most of PFAS. Oxidative additives, as well as surfactants, may enhance the performance of the technique, which is also affected by organic matter, residual solvents, pH and temperature of the solution. PFAS concentration is a crucial factor in terms of treatment efficiency since it defines the rate order, while differences in functional group, chain length, and extent of fluorination affect hydrophobicity, surface activity and thermal activation energy of PFAS. Reaction pathways, solution chemistry, reactor configuration, and operational parameters including flowrate, atmosphere condition, US frequency and power density are discussed within this critical review, with the aim of boosting the implementation of this technology for PFAS remediation.